2020
DOI: 10.1111/ecog.05135
|View full text |Cite
|
Sign up to set email alerts
|

Interaction networks of avian mixed‐species flocks along elevation in the tropical Andes

Abstract: Ecological communities are comprised of species that interact with each other and those interactions ultimately generate community structure. Network theory provides a useful framework to study communities, by simultaneously considering species composition and the interactions among species. In this study, I use mixed-species flocks as model systems to gain insights on community and network structure. Specifically, I use co-occurrence network analyses to explore if avian mixed-species flocks change in richness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 69 publications
5
40
0
5
Order By: Relevance
“…Code and data used for analyses are available from the Dryad Digital Repository (and in Supporting information) <http://dx.doi.org/10.5061/dryad.fxpnvx0qj> (Montaño‐Centellas et al 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…Code and data used for analyses are available from the Dryad Digital Repository (and in Supporting information) <http://dx.doi.org/10.5061/dryad.fxpnvx0qj> (Montaño‐Centellas et al 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the identity of species participating in flocks can be influenced by vegetation structure and the presence of exotic trees. Changes in species composition of flocks related to land‐use change have been described in multiple ecosystems (Brandt et al, 2009; Jones & Robinson, 2020; Montaño‐Centellas, 2020; Thomson & Ferguson, 2007). In our study, the variation in species composition among flocks was driven by differences in habitat affinities of a small number of the flocking species.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction networks were constructed using the “group gambit” method (Franks et al, 2010), which defines all the individuals of a group of animals observed at any given time as associated (Whitehead & Dufault, 1999). This method assumes interactions among all the species that were part of a flock and is a common method employed in networks of mixed‐species flocks (Mokross et al, 2014; Montaño‐Centellas, 2020; Zhou et al, 2019). To build weighted networks, we used the frequency of co‐occurrence of species in flocks within a transect during each sampling period.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations